Mobilidade urbana sustentável em Francisco Beltrão : uma cidade de porte médio do Paraná - Junior, Ertal de Vasconcelos Oliveira (Universidade do Vale do Rio dos Sinos, 2017)
To present a diagnosis with suggestions for implementing policies for sustainable mobility in medium-sized cities is the objective of this research. The suggestions put forward here intend to restructure the transit and transport system, promoting social inclusion, prioritizing for short and medium distances the modes on foot and bicycle and for the greater distances collective transportation. Thus, a set of propositions arises with the intention of changing the existing mobility patterns, transforming it within a logic of sustainability. However, the main contribution of this study is the use of mobility strategies for midsize cities, with priority being given to pedestrians, cyclists and users of public transport. We use qualitative and quantitative research and case study. Interviews were conducted with users of motorized, non-motorized public transport (cyclists) and with special needs users using public transport. The sample selected answered a questionnaire structured with questions that aim to identify their perception in relation to the transportation used. Interviews were also conducted with people with special needs who use public transport, and the headquarters of the ADFVFB (Association of Physically and Visually Impaired People of Francisco Beltrão) were used. The interviews directed to Ciclovia users were made with the Pedala Beltrão Cyclists Group. About 61% of the interviewees do not own their own vehicles and need public transportation to travel in the municipality, 58% evaluate how to regulate the general conditions of public transportation in the municipality. , Followed by 25%, which stands out due to the poor conservation of the sidewalks, followed by 18% of bad signposts for pedestrians. One of the biggest difficulties of accessibility and mobility in the city of Francisco Beltrão for the president of ADFVFB is access, mainly in commerce and In many public bodies. And now another major difficulty that is currently emerging is with regard to housing, there are not many options for affordable housing for people with disabilities, whether it is motor or sensory, in the visual or auditory case. At the end, the study presented a suggestion for the restructuring of the transit and transportation system, promoting social inclusion, prioritizing for short and medium distances the modes on foot and bicycle and for the greater distances collective transportation; Increasing the number of collective transportation routes; Improving the quality of collective transportation; Encouraging the use of non-motorized modes; Adapting streets for pedestrians and wheelchairs and blocks on a human scale to encourage the flow of people; Integrate bicycle transport with public transportation, among others.
Keywords: Usuário; Transporte público motorizado; Bicicletas; Mobilidade sustentável; User; Motorized public transport; Bicycles; Sustainable mobility; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo